Efficacy of two different microbial consortia on salinity tolerance in chickpea: an in‑planta evaluation on biochemical, histochemical, and genomic aspects - Sathya, A.; Rehman, V.; Srinivas, V.; Kudapa, H.; Gopalakrishnan, S. (2024)
This study aimed to identify and characterize actinobacteria and rhizobia with plant growth-promoting (PGP) traits from chickpea plants. Out of 275 isolated bacteria, 25 actinobacteria and 5 chickpea rhizobia showed 1-aminocyclopropane-1-carboxylate deaminase (ACCd) activity. Selected chickpea rhizobia were tested for their nodulating capacity under sterile and non-sterile soil conditions. Further screening on salinity and PGP traits identified three promising isolates: Nocardiopsis alba KG13, Sinorhizobium meliloti KGCR17, and Bacillus safensis KGCR11. These three isolates were analyzed for their compatibility and made into a consortium (Consortium 1). This along with another consortium made from our salinity-tolerant lab strains Chryseobacterium indologenes ICKM4 and Stenotrophomonas maltophilia ICKM15 (Consortium 2) was compared in planta studies. Trials revealed that Consortium 2 showed significant (p < 0.05) tolerance and on above-ground, below-ground traits and yield components than Consortium 1. Moreover, both consortia induced nodulation in saline-stressed plants, alleviated electrolyte leakage (2.3 vs. 0.4 in ICCV 2; 1.8 vs. 0.6 in JG 11), and increased chlorophyll content. Histochemical staining indicated reduced oxidative stress and lipid peroxidation in consortium-treated plants under salinity stress. Further, gene expression studies revealed mixed patterns, with up-regulation of antioxidant and transporter genes observed in consortium-treated plants, particularly in Consortium 2. Overall, Consortium 2 showed better gene expression levels for antioxidant and transporter genes, indicating its superior efficacy in mitigating salinity stress in chickpea plants. This study provides valuable insights into the potential use of these microbial isolates in improving chickpea productivity by enhancing salinity tolerance.